An integrated model for warehouse design and planning - Geraldes, Carla A.S. (2014)
Warehouse design is a field of interest for both practitioners and researchers that have attracted a lot of research attention in the last years. Nevertheless it remains a complex task with very few general models that capture the existing and often conflicting trade-offs of a warehouse system. Literature surveys show that most research efforts have been devoted to solve limited and well-defined problems rather than integrated ones. This is not surprising since developing an integrated model is more difficult to analyse and treat analytically. In this talk we present and discuss a high-level model that integrates some decisions involved in warehouse design and planning. Our aim is to analyse the value of integrating warehouse decisions showing that additional savings can be achieved.